2021
DOI: 10.1111/eva.13297
|View full text |Cite
|
Sign up to set email alerts
|

Domestication‐induced reduction in eye size revealed in multiple common garden experiments: The case of Atlantic salmon (Salmo salar L.)

Abstract: Domestication leads to changes in traits that are under directional selection in breeding programmes, though unintentional changes in nonproduction traits can also arise. In offspring of escaping fish and any hybrid progeny, such unintentionally altered traits may reduce fitness in the wild. Atlantic salmon breeding programmes were established in the early 1970s, resulting in genetic changes in multiple traits. However, the impact of domestication on eye size has not been studied. We measured body size correct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 133 publications
(120 reference statements)
1
3
0
Order By: Relevance
“…In contrast, our study revealed significant differences in growth parameters between farmed and wild salmon, with the hybrids displaying intermediate characteristics. These results align with previous reports investigating wild, hybrid and farmed fish kept in common conditions (Glover et al, 2009; Perry et al, 2021; Thodesen et al, 1999). Specific growth rate (SGR) and body condition (κ factor) are commonly used metrics in salmonid aquaculture to assess growth and quality, respectively.…”
Section: Discussionsupporting
confidence: 93%
“…In contrast, our study revealed significant differences in growth parameters between farmed and wild salmon, with the hybrids displaying intermediate characteristics. These results align with previous reports investigating wild, hybrid and farmed fish kept in common conditions (Glover et al, 2009; Perry et al, 2021; Thodesen et al, 1999). Specific growth rate (SGR) and body condition (κ factor) are commonly used metrics in salmonid aquaculture to assess growth and quality, respectively.…”
Section: Discussionsupporting
confidence: 93%
“…Another gene found in this region is rpgr , which has been linked to the vision ability in domesticated chickens (Wang, Zhang, et al., 2016). Vision appears to be a feature affected by domestication in fishes, as evidenced by the smaller eye size observed in domesticated Atlantic salmon (Perry et al., 2021). Additionally, the six6 gene involved in eye development in vertebrates (Pritchard et al., 2018) is also relevant in this context.…”
Section: Discussionmentioning
confidence: 99%
“…Adaptation to captivity is well documented in salmon, where a relatively homogeneous captive environment can increase the efficacy of selection pressures resulting from high population density, release from predation, and abundant nutritious food (Fleming & Einum, 1997 ; Wessel et al., 2006 ; Zhang et al., 2016 ). Salmon traits hypothesized to evolve in response to culture conditions include fast growth (Fleming et al., 2002 ), a reduced antipredator behavior (Jackson & Brown, 2011 ), and reduction in eye size (Perry et al., 2021 ). These domestication traits could be maladaptive under natural conditions (e.g., reduced eye size in the captive condition is a maladaptive trait selected against in the wild) (Perry et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Salmon traits hypothesized to evolve in response to culture conditions include fast growth (Fleming et al., 2002 ), a reduced antipredator behavior (Jackson & Brown, 2011 ), and reduction in eye size (Perry et al., 2021 ). These domestication traits could be maladaptive under natural conditions (e.g., reduced eye size in the captive condition is a maladaptive trait selected against in the wild) (Perry et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%